2010
DOI: 10.1211/jpp.62.03.0004
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics of morphine and its glucuronide conjugate in a rat model of streptozotocin-induced diabetes and the expression of MRP2, MRP3 and UGT2B1 in the liver

Abstract: In STZ-diabetic rats, the distribution volume of morphine increased, the glucuronidation rate and M3G transportation into the blood were enhanced, and the excretion of M3G was decreased, leading to an increase in the plasma M3G concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 13 publications
2
19
0
Order By: Relevance
“…This is consistent with numerous earlier reports of a significant reduction in the antinociceptive potency of morphine that was associated with hyperglycemic state in diabetes [4,5,24]. Alteration in the µ-opioid receptor function, an increase in the levels of interleukin-1b, and accumulation of morphine-3-glucuronide were reported in diabetic rats [9]. Repeated (21 days) administration of venlafaxine (10 mg/kg, po) was reported to suppress mechanical hyperalgesia in STZ-induced diabetic rats, whereas a single administration of the drug reduced it only slightly.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with numerous earlier reports of a significant reduction in the antinociceptive potency of morphine that was associated with hyperglycemic state in diabetes [4,5,24]. Alteration in the µ-opioid receptor function, an increase in the levels of interleukin-1b, and accumulation of morphine-3-glucuronide were reported in diabetic rats [9]. Repeated (21 days) administration of venlafaxine (10 mg/kg, po) was reported to suppress mechanical hyperalgesia in STZ-induced diabetic rats, whereas a single administration of the drug reduced it only slightly.…”
supporting
confidence: 92%
“…The animals often display polyuria, diarrhea, and a gradual reduction in body weight. Some authors demonstrated that STZ treatment altered the expression of cytochromes P450 1A2, 2B1 and 4A in rat models of diabetes, which may induce changes in pharmacokinetics of experimental substances [9]. Diabetic rats exhibit many complications seen in patients with diabetic neuropathy, including hyperalgesia and progressive loss of sensory nerve conduction, impaired intraneuronal blood flow as well as micro-and macrovascular reactivity.…”
mentioning
confidence: 99%
“…Studying M6G activity in rodents is complicated, because although morphine is metabolized to both glucuronides by human UGT2B7, rodent Ugt2b1 metabolizes morphine exclusively to M3G (Kuo et al, 1991;Salem and Hope, 1997;Hasegawa et al, 2009). Nevertheless, hepatic-derived M3G and exogenously administered M6G are substrates for human and rodent MRP2/Mrp2 and MRP3/Mrp3, which are responsible for their hepatobiliary disposition (Zelcer et al, 2005;van de Wetering et al, 2007;Hasegawa et al, 2010). Biliary excretion, representing up to 20% of morphine glucuronide clearance (Garrett and Jackson, 1979;Ouellet and Pollack, 1995), is mediated by Mrp2.…”
Section: Introductionmentioning
confidence: 99%
“…Biliary excretion, representing up to 20% of morphine glucuronide clearance (Garrett and Jackson, 1979;Ouellet and Pollack, 1995), is mediated by Mrp2. Previous studies examined the pharmacokinetics of M3G in rats with streptozotocininduced diabetes and bile duct ligation-induced cholestasis (Hasegawa et al, 2009(Hasegawa et al, , 2010. Both disease states altered the expression of Ugt2b1, Mrp3, and Mrp2 and negatively affected the biliary excretion of M3G.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperglycemia with DM affects not only the physiological condition of the patient but also often the pharmacokinetics of a drug; the non-enzymatic glycation of serum albumin was shown to influence the protein binding of certain drugs, which is one of the most important factors for the distribution of drugs doi: 10.7243/2053-7107-2-1 [13], and the activities/expressions of serum esterases and drug-metabolizing enzymes were also shown to be altered in DM [14,15]. These alterations have the ability to affect the pharmacokinetics of AS and DHA.…”
Section: Introductionmentioning
confidence: 99%